2018
DOI: 10.5604/01.3001.0012.2114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proton Pump Inhibitors on Mortality in Patients with Cirrhosis and Spontaneous Bacterial Peritonitis

Abstract: Introduction and aim. Spontaneous bacterial peritonitis (SBP) is a life-threatening infection in patients with cirrhosis. However, it is unknown whether patients with SBP and cirrhosis who do not have active gastrointestinal bleeding have a poorer prognosis if treated with proton pump inhibitors (PPI). Material and methods. We used the Taiwan National Health Insurance Database to identify 858 patients with SBP and cirrhosis who were administered PPIs and hospitalized between January 1, 2010, and December 31, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Dultz et al[16] reported PPI use to be an independent predictor of mortality in patients with compensated and decompensated liver cirrhosis [HR = 2.33, (1.26–4.29); P = 0.007], but another study performed on hospitalised cirrhotic patients did not show a difference in survival between PPI users and non-users[13]. Hung et al[17] studied the effect of inpatient PPI use on survival in cirrhotic patients admitted with HE and reported a higher 30-d mortality in the PPI group (HR = 1.360, (1.208-1.532); P < 0.001], but not in their separate study of patients with SBP[18]. These studies have not shown consistent results on the association of PPI use and mortality, which could potentially be related to issues with defining the duration of PPI exposure and the classification of PPI user status, leading to potential biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dultz et al[16] reported PPI use to be an independent predictor of mortality in patients with compensated and decompensated liver cirrhosis [HR = 2.33, (1.26–4.29); P = 0.007], but another study performed on hospitalised cirrhotic patients did not show a difference in survival between PPI users and non-users[13]. Hung et al[17] studied the effect of inpatient PPI use on survival in cirrhotic patients admitted with HE and reported a higher 30-d mortality in the PPI group (HR = 1.360, (1.208-1.532); P < 0.001], but not in their separate study of patients with SBP[18]. These studies have not shown consistent results on the association of PPI use and mortality, which could potentially be related to issues with defining the duration of PPI exposure and the classification of PPI user status, leading to potential biases.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly concerning as PPIs are metabolised in the liver by cytochrome CYP450[11,14], and as a result, their half-life increases by 4-8 h in cirrhotic patients[15]. There have been concerns that PPI use increases the risk of mortality in patients with decompensated liver disease[16], and those with HE[17], but other studies dispute the association of mortality with PPI use in decompensated cirrhosis or cirrhotic patients with SBP[13,18]. Of the published data on PPI use and mortality in cirrhotic patients[13,16,17], “PPI users” are often defined as patients with PPI prescriptions at the study inclusion, and PPI dose duration is not measured.…”
Section: Introductionmentioning
confidence: 99%
“…85,105 A study has concluded that PPIs do not increase short-term mortality in patients with SBP without active gastrointestinal bleeding, but do increase the long-term risk of death. 106 Moreover, PPIs have been described as possibly worsening the disease course of SBP by increasing the risk of acute kidney injury and severe HE. 105 Although PPIs may indeed be related to SBP through related mechanisms, the relationship between PPIs and the risk of SBP is still inconclusive and more well-designed prospective studies are needed to help clarify this relationship.…”
Section: Ppis and Sbpmentioning
confidence: 99%
“…(73) Greater PPI exposure has also been reported to increase the risk of liver-related hospitalization and mortality. (74,75) In critically ill patients with decompensated cirrhosis admitted to a medical ICU, NSAIDs were associated with 46.1% of the instances of preventable medication-related harm, including melena or hematemesis and worsening renal function (reduced creatinine clearance). (14) Other studies demonstrated a decreased glomerular filtration rate by ~30% in patients with compensated cirrhosis, (42,43) explained by the inhibition of prostaglandin synthesis, which decreases vasodilation of the afferent renal arterioles.…”
Section: Medication Pkpd Change Clinical Impact Remarksmentioning
confidence: 99%